InSight@unimas : Teaching and Learning Bulletin, vol.31/2020 - Universiti Malaysia Sarawak, Centre for Applied Learning and Multimedia (Centre for Applied Learning and Multimedia, 2020)
During the enforcement of Movement Control Order (MCO), all higher learning institutions have been ordered to temporarily halt all activities related to teaching and learning. Lecturers were instructed to make transition to online learning by converting their usualy face-to-face classes into virtual classes either live conferencing or through the learning management system